Liver Fluke Control in Beef Cattle - Max B. Irsik; Charles H. Courtney, III; Ed Richey (EDIS)
Revised! VM-120, a 5-page illustrated fact sheet by M.B. Irsik, Charles Courtney III, and Ed Richey, describes the control of Fasciola hepatica, one of the most damaging parasites in Florida cattle — its life cycle, damage to the animal and industry, life cycle of the intermediate host, diagnosis of liver fluke infection, and control of the liver fluke. Published by the UF College of Veterinary Medicine Large Animal Clinical Sciences Department, July 2007.